Unsur Akulturasi Budaya pada Rumah Tjong A Fie di Kota Medan - Rudiansyah .; Gugun Gunardi; Widyo Nugrahanto (Pascasarjana ISBI Bandung, 2019)
That the Chinese began to immigrate to Indonesia, especially in Medan city was in the early 12nd century. In the meantime they also introduced their religion, art and culture to the local people. ‘The acculturation refl ected on Tjong A Fie’s Residence’ is selected as the title of the thesis with the purpose of assessing and understanding the acculturation that was discovered on the buildings with Chinese style in Medan City. This research was focused on the objects of Tjong A Fie’s residence.This research used John W. Berry’s acculturation theory; while the method that is used is the qualitative descriptive method.An acculturation is a prosess that happens when one group of people with some kind of culture confronts the elements of some other culture. From this comes into being the change of the original cultures, yet these two cultures have not lost the elements of their own cultures. The acculturation can be seen on part of Tjong A Fie’s residence like the gold color that was used dominatedly, the pictures on the cloth and the melaysian special window shapes. The elements of European culture can be seen on the strut, the decorative lamp, the table and the sculptures of the ceiling of Tjong A Fie’s residence. The elements of Chinese culture can be found on the strut of the front gate, the sculptures of lion, the sculptures on the wall, the entrance door as well as the shape of the curving roof that stands for the special structures of house in China.Keywords: acculturation, Chinese house, Tjong A Fie